PERAN PENYULUH PERTANIAN DALAM MENGEMBANGKAN KEGIATAN USAHATANI SAYURAN DI DESA PUUNGGONI KECAMATAN ANGATA KABUPATEN KONAWE SELATAN - Mansyar Lamatungga; Sitti Rosmalah; Hartati Hartati (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
This research aims to describe the Agricultural extension agent’s role in developing vegetable farming in Puunggoni Village, Angata District. This research uses qualitative descriptive research. The sample in this study was 30 vegetable farmers in Puunggoni Village, Angata District, who were selected at simply random from a population of 60 people. The data sources in this research are primary and secondary data. The data collection technique used interviews using a list of questions (questionnaire) and observation. The variable used to measure the role of extension agents is farmers' perceptions of extension agents as technology transfer agents, facilitators, dynamists, and organizers. Variables are measured using the Likert Scale Summated Rating (SLR). The Likert scale in this study was used for farmers based on the answers given, which consisted of 5 categories, namely very good (score 5), good (score 4), quite good (score 3), not good (score 2), and very poor. good (score 1). The research results show that agricultural extension workers play a very good role as technology transfer agents, facilitators, and dynamists.